(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Talc’s ability to absorb moisture and oil makes it nutritious makes it an attractive choice for use in the food industry, where it is powdered added to prevent clumping or solidification of foods can also be an anti-caking agent in processed foods works as Its properties make talc a valuable mineral in many fields. provides functional and aesthetic benefits. This article is about talc in the food industry about the fact that scientific work has been carried out on the harmful aspects of its use information provided.